2015
DOI: 10.1007/s11695-015-1635-5
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in Perioperative Anesthetic Management of the Morbidly Obese: I Am a Surgeon, Why Should I Care?

Abstract: Over the last four decades, as the rates of obesity have increased, so have the challenges associated with its anesthetic management. In the present review, we discuss perioperative anesthesia management issues that are modifiable by the early involvement of the surgical team. We sum up available evidence or expert opinion on issues like patient positioning, postoperative analgesia, and the effect of continuous positive airway pressure (CPAP) ventilation on surgical anastomosis. We also address established pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 89 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…[7][8][9] Obesity represents a surgical challenge for spine surgeons and is significantly associated with a longer operation time and an increased intraoperative blood loss. 10 However, there is conflicting evidence in the literature regarding postoperative outcomes after lumbar fusion in obese patients. While some authors showed similar improvements in pain status, functional outcome, and health-related quality of life (HRQoL), [11][12][13][14][15] others have reported worse clinical results in obese patients.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Obesity represents a surgical challenge for spine surgeons and is significantly associated with a longer operation time and an increased intraoperative blood loss. 10 However, there is conflicting evidence in the literature regarding postoperative outcomes after lumbar fusion in obese patients. While some authors showed similar improvements in pain status, functional outcome, and health-related quality of life (HRQoL), [11][12][13][14][15] others have reported worse clinical results in obese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Global projections anticipate a rise in obesity from around 13% in 2016 [6] to 23-27% by 2035 [7]. The escalating incidence of obesity has led to a proportional increase in bariatric surgeries [8], posing greater challenges to anesthesiologists in the perioperative period [9]. Obesity is associated with increased incidence and severity of postoperative complications [10].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with morbid obesity are having a higher prevalence of OSA and further more increase in co-existing medical diseases [3] [4] [5].…”
Section: Introductionmentioning
confidence: 99%